Озеленення міста Хмельницького в другій половині ХХ ст. - Ганаба, Дмитро; Hanaba, Dmytro (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглянуто особливості озеленення міської інфраструктури Хмельницького в другій половині ХХ ст. На основі документів відділу міського комунального господарства проаналізовано стан озеленення міста. Указано на масштабність комплексу заходів з озеленення, що здійснювалися на основі партійних і державних програм. Позитивний фактор у процесі озеленення – залучення громадськості у висадці та догляді за молодими насадженнями. Характерним недоліком у процесі озеленення, що набуває поглиблення й дотепер, є без- системність у доборі асортименту рослин, незначна різноманітність їх видового складу, відсутність наукового підходу в проектах озеленення міста тощо. У процесі озеленення практично не враховували кліматичних характеристик міської території, санітарно-гігієнічних умов й екологічних особливостей урбанізованого середовища тощо. The article discusses the features of greening urban infrastructure of Khmelnytskyi in the second half of the twentieth century. It is noted that the relevance and importance of this problem stems from the needs of creating a sustainable urboekological system, improvement of sanitary and hygienic conditions and comfortable aesthetic rest of the people in the city. Based on the analysis of documents city municipal department analyzed greening the city . Specified the magnitude of a complex of actions on gardening, was carried out on the basis of party and government programmes. The feature of landscaping Khmelnitsky which survived and till nowadays is a connection with national holidays and anniversaries. A positive factor in the process of landscaping was the involvement of the public in planting large number of trees and shrubs and care for young plantings. The practice of using the efforts of the public in plant conservation and increase the number and range of parks, squares and streets should be considered in future plans for landscaping. The characteristic deficiency in the process of gardening that becomes a deepening, and still is unsystematic in choosing the variety of plants, a small variety of their species composition, the lack of a scientific approach to the landscaping projects of the city. In the process of landscaping were hardly taken into account the climatic characteristics of the urban area, sanitary conditions and environmental features of the urban environment.
Greening of the City Khmelnitsky in the Second Half of the Twentieth Century.
Keywords: деревні насадження; рослини; методи; комплекс заходів; урбоекологічна система; озеленення; tree planting; plants; methods; a set of measures; urboecological system; landscaping